Heterogeneous electrode processes and localized corrosion - Tan, Yongjun, 1963- (Hoboken, N.J. : Wiley, 2013)
"This book covers the areas of electrochemical heterogeneity and electrode inhomogeneity and their effects on nonuniform electrode processes, in particular, localized corrosion. It covers the fundamentals, experimental methods, and engineering aspects of electrochemical heterogeneity"--
Machine generated contents note: Preface Chapter I. Homogeneous Electrode Models and Uniform Corrosion Measurements 1.1 Homogeneous electrodes and traditional electrochemical methods 1.2 Mixed electrodes and uniform corrosion models 1.3 The mixed potential theory and electrochemical corrosion measurement 1.4 Electrochemical impedance investigation of electrode-solution interface 1.5 Electrochemical noise monitoring of rapid electrode processes 1.6 Issues and difficulties in traditional electrochemical methods Chapter II. Probing Electrode Inhomogeneity, Electrochemical Heterogeneity and Localized Corrosion 2.1 Probing electrode inhomogeneity 2.2 Probing electrochemical heterogeneity and localized corrosion 2.3 Overview of various techniques for probing localized corrosion Chapter III. Visualizing Localized Corrosion Using Electrochemically Integrated Multi-Electrode Arrays 3.1 An electrochemically integrated multi-electrode array, the wire beam electrode 3.2 Visualizing the progression of localized corrosion in an Evans water drop 3.3 Visualizing localized corrosion in environments with ion concentration gradients 3.4 Visualizing localized corrosion by the WBE in conjunction with scanning probes Chapter IV. Measuring Thermodynamic and Kinetic Parameters from Localized Corrosion Processes 4.1 Methods of probing localized corrosion thermodynamics and kinetics 4.2 Measuring localized corrosion using the overpotential-galvanic current method 4.3 Measuring localized corrosion using the galvanic current method 4.4 Measuring localized corrosion using the Rn-WBE method Chapter V. Characterizing Inhomogeneity and Localised Corrosion on Coated Electrode Surfaces 5.1 Characterising inhomogeneities in organic coatings and inhibitor films 5.2 Characterising inhomogeneity in organic coatings using the WBE method 5.3 The effects of coating inhomogeneity on electrochemical measurement 5.4 Visualisng underfilm corrosion and the effects of cathodic protection 5.5 Studying corrosion protection by coatings and cathodic protection Chapter VI. Designing Experiments for Studying Localized Corrosion and Its Inhibition in Inhomogeneous Media 6.1 Basic issues in localized corrosion and inhibitor test design 6.2 Fundamental considerations in selecting corrosion measurement techniques 6.3 Designing corrosion tests in highly-resistive and inhomogeneous media 6.4 Case studies: Designing crevice corrosion tests by means of the WBE 6.5 Case study: Designing experiments for localized corrosion inhibitor discovery Chapter VII. Sensing Localized Electrodeposition and Electrodissolution 7.1 Experimental methods for sensing localized electrodeposition and dissolution 7.2 Sensing localized electrodeposition using the WBE 7.3 Sensing localized electrodissolution using the WBE 7.4 Sensing nonuniform electrochemical deposition of organic coatings Chapter VIII. Versatile Heterogeneous Electrode Processes 8.1 Scanning and modeling various heterogeneous electrode processes 8.2 Electrochemical noise generation from electrochemical heterogeneity 8.3 Harvesting electrical power from electrochemical using the WBE 8.4 Further research issues on electrochemical heterogeneity.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Corrosion and anti-corrosives.; Heterogeneous catalysis; Electrocatalysis; Electronic books